VARIACION ESTACIONAL DE LAS POBLACIONES DE PSOROPHORA SPP. (DIPTERA: CULICIDAE) Y DETECCION DE SUS PARASITOS Y PATOGENOS EN LA PROVINCIA DE BUENOS AIRES, ARGENTINA - Campos, Raúl E.; Macia, Arnaldo; García, Juan J. (Acta Entomológica Chilena, 2022)
A two-year study on the population ecology of Psorophora species was conducted in various distinct limnotopes alongside Río de la Plata, in the northeast of Buenos Aires Province, Argentina. Larvae and pupae of three species (Ps. ciliata, Ps. cyanescens and Ps. ferox) were collected from September to April. Population density varied widely according to water level of the flooded habitat and ambient air temperatures. From October to May, adults of six species were captured employing CDC light traps. Additionally to the three species above, Ps. varinervis, Ps. discrucians and Ps. varipes were collected. For both, larval and adult stages, Ps. ferox was by far the most frequent species in the survey. Occurrence of Ps. ferox appears to be positively correlated with shaded pools in gallery forest. Fungal Smittium morbosum var. rioplatensis López Lastra) and microsporidian (Amblyospora ferocis García & Becnel) infections were recorded in larvae of Ps. ferox. Spores of an unidentified microsporidia and filarial larvae were also detected in adults of Ps. ferox